2020
DOI: 10.2308/tar-2017-0235
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Accounting Interviewing: A Comparison of Real and Virtual Accounting Interviewers

Abstract: Recent technological advances make it possible to create automated, virtual interviewers, called embodied conversational agents (ECAs). We study how an ECA compares to a human interviewer in three experiments. In experiment 1, we show that two theoretically motivated factors-making the ECA facially and vocally similar to the interviewee-result in the ECA performing similarly to or better than human interviewers for six antecedents of disclosure quality. In two additional experiments, we show that employees are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 90 publications
0
18
0
Order By: Relevance
“…Thus, it is unclear if auditees' disclosure behavior, auditors' skepticism, and the likelihood of follow-up questions in these situations would be more similar to face-to-face interactions or email communications. There is some prior research that shows auditees are more likely to disclose information to a virtual interviewer (i.e., an avatar) than to a human internal auditor (Pickard et al 2020); however, in the case of remote auditing, the auditee is still interacting with and disclosing to another live human. Thus, it is unclear that the results from this prior research would generalize more broadly to remote auditing as it is conducted today.…”
Section: Remote Auditingmentioning
confidence: 99%
“…Thus, it is unclear if auditees' disclosure behavior, auditors' skepticism, and the likelihood of follow-up questions in these situations would be more similar to face-to-face interactions or email communications. There is some prior research that shows auditees are more likely to disclose information to a virtual interviewer (i.e., an avatar) than to a human internal auditor (Pickard et al 2020); however, in the case of remote auditing, the auditee is still interacting with and disclosing to another live human. Thus, it is unclear that the results from this prior research would generalize more broadly to remote auditing as it is conducted today.…”
Section: Remote Auditingmentioning
confidence: 99%
“…Our study makes several important contributions to prior research and to practice. From a broad perspective, we contribute to the expanding line of research that is testing the effectiveness of emerging technologies within accounting settings (e.g., Dowling and Leech 2014;Pickard et al 2020;Hodge et al 2021;Austin et al 2021;Christ, Emett, et al 2021). This line of research has found mixed results regarding technology effectiveness, leaving many to question whether these emerging technologies have failed to achieve their expected benefits within accounting settings (Chen et al 2014;Han et al 2016;Fersht 2017;Reed 2018;Information Age 2019;Eulerich, Masli, et al 2021).…”
mentioning
confidence: 99%
“…Further, since this is among the first study to explore IAs in accounting, our operationalization of the IAs in our setting was kept very simple, with a short description of an IA and a picture of a desktop computer. A large literature exists on several other attributes of intelligent agents, including physical presence, anthropomorphism, and dynamic interaction, among others (Pickard, Schuetzler, Valacich, and Wood 2019). Future research could investigate how one or more of these attributes impact manager decision-making and could decrease managers' "explainability" for the results produced by an IA, which may affect aggressive financial reporting.…”
Section: Discussionmentioning
confidence: 99%